From plate to palate: Bridging nutrition and pediatric dental health - R. V. Swetha; Vishnu Rekha Chamarthi; A. K. R. Santhosh Priya; Dhanraj Kalaivanan; Santham Krishnamoorthy; Sumaiyya Saleem; Sai Sarath Kumar Kothimbakkam (Journal of Oral Research and Review)
Oral health and nutrition share a dynamic, bidirectional relationship that significantly influences systemic health and overall well-being. Adequate nutrition, encompassing a balanced intake of macronutrients and micronutrients, is fundamental for the optimal development, maintenance, and function of oral structures. Nutritional imbalances whether due to deficiencies or excesses can compromise oral health, contributing to conditions such as dental caries, periodontal disease, enamel hypoplasia, and delayed eruption patterns. Emerging evidence highlights that oral manifestations frequently serve as early indicators of systemic nutritional inadequacies, underscoring the oral cavity as a mirror of general health. Despite the well-established systemic implications of nutrition, its specific impact on pediatric oral health remains underexplored. This review aims to consolidate current insights between nutrition and oral health, with a focus on the impact of dietary patterns, nutrient deficiencies, and malnutrition on developing dentition. By emphasizing this synergy, this review advocates for an integrated approach to pediatric healthcare that bridges nutrition and dentistry for improved long-term outcomes.